دور انخفاض المهر في تسهيل الزواج للشباب والحد من الرذائل الأخلاقية في المجتمع الأفغاني: The role of lowering the dowry in facilitating marriage for young people and reducing moral vices in Afghan society - Ullah, Zaki Zakir; Awang, Abdul Bari; B Zakaria, Mohamad Sabri (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
ملخص البحث تهدف هذه الدراسة إلى دور انخفاض المهر في تسهيل الزواج للشباب والحد من الرذائل الأخلاقية في المجتمع الأفغاني. فالإسلام قد رغب إلى الزواج وتخفيف المهور وتيسيرها، وأن غلاء المهور فوق طاقة الشباب أمر غير عقلاني وأخلاقي وشرعي، ومع الأسف الشديد هناك بعض العوائق أمام زواج الشباب و خاصة الأفغاني، ومنها غلاء المهور وتكاليف الزواج. وهناك أسباب كثيرة لغلاء المهور، ومنها تظاهر الشباب بالمال، وزيادة الطموح من البنات و العائلات، وتدخل النساء في الأمور المالية، وعدم فهم الصحيح من الدين، والتقاليد المهلكة، ووسائل الإعلام الأجنبية والغربية، وغيرها. وكذلك هناك أضرار سلبية واجتماعية كثيرة لغلاء المهور ومنها الضغوط المالية وانهيار الأسر، وزيادة معدل الطلاق والجرائم، وسلب الثقة الاجتماعية، والفجور الجامع الأخلاقية، و تفشي العنوسة بين الجنسين، وقد أدت كثرة المهور إلى عدم تسهيل الزواج للشباب الأفغاني كما أجاب المجيبون بها في المقابلات. وقد استخدم الباحث في هذا البحث المنهج الكيفي و أقام بجمع البيانات من الكتب، و الرسائل، والمقالات وعن طريق المقابلات مع الخبراء والمتخصصين. وتوصل الباحث إلى أن لحل هذه المشكلة طريق كثيرة ومنها التوعية الشعبية، والفهم الصحيح من الدين، وترك التقاليد، وترغيب الشباب إلى الزواج بواسطة العائلات والحكومات، والحد من كثرة المهور وتحديد المقدار العقلاني والمنطقي والعادل؛ حتى تسهل سبل الزواج للشباب الأفغاني. ABSTRACT Abstract: This study aims to explore the role of lowering dowries in facilitating marriage for youth and reducing moral vices in Afghan society. Islam encourages marriage and the reduction and facilitation of dowries, and the high cost of dowries beyond the capacity of young people is unreasonable, unethical, and un-Islamic. Unfortunately, there are several obstacles to youth marriage, especially for Afghans, including the high cost of dowries and wedding expenses. There are many reasons for the high dowries, including young people's display of wealth, increased aspirations from girls and families, women's interference in financial matters, misunderstandings of religion, destructive traditions, foreign and Western media influences, and more. Additionally, there are many negative social impacts of high dowries, such as financial pressure, family breakdowns, increased divorce rates and crimes, loss of social trust, moral corruption, and the prevalence of singlehood among both genders. The high dowries have made it difficult for Afghan youth to marry, as indicated by the respondents in the interviews. The researcher employed a qualitative approach in this study, gathering data from books, letters, articles, and through interviews with experts and specialists. The researcher concluded that there are many ways to solve this problem, including public awareness, a correct understanding of religion, abandoning harmful traditions, encouraging youth to marry through families and governments, and limiting the high dowries by setting reasonable, logical, and fair amounts; thus, facilitating marriage for Afghan youth.